Idiopathic multiple pigmented hemorrhagic sarcoma or Kaposi disease - Chirinos M., José (1952)
This paper seeks to publish the first case of Kaposi's disease studied in Lima. This disease, its rarity in our environment, is difficult to diagnose. This case was diagnosed with the cooperation of the Institute of Pathology of Prof. P. Weiss.